Association of Plasma γ′ Fibrinogen With Incident Cardiovascular Disease: The Atherosclerosis Risk in Communities (ARIC) Study. Issue 12 (December 2015) - Appiah, Duke; Schreiner, Pamela J.; MacLehose, Richard F.; Folsom, Aaron R.
Abstract : Objectives—: To prospectively examine the association of plasma γ′ fibrinogen with the incidence of multiple cardiovascular disease (CVD) end points, independent of established CVD risk factors, total fibrinogen, and other inflammatory markers. Approach and Results—: The Atherosclerosis Risk in Communities (ARIC) study measured γ′ fibrinogen by enzyme-linked immunosorbent assay in stored plasma samples from 1993 to 1995 and related levels in 10 601 adults to incident CVD end points (coronary heart disease [n=1603], ischemic stroke [n=548], peripheral artery disease [n=599], heart failure [n=1411], and CVD mortality [n=705]) through 2012 (median follow-up, 18 years). In Cox models accounting for established CVD risk factors and total fibrinogen levels, γ′ fibrinogen was associated positively with peripheral artery disease (hazard ratio [HR] per 1-SD [8.80 mg/dL] increment, 1.14 [1.04–1.24]), heart failure (HR, 1.06 [1.01–1.13]), and CVD deaths (HR, 1.12 [1.04–1.21]) but not with incident coronary heart disease (HR, 1.01 [0.96–1.07]) or ischemic stroke (HR, 0.98 [0.89–1.07]). Additional adjustment for C-reactive protein, however, eliminated the associations with peripheral artery disease and heart failure. Conclusions—: These findings do not lend support to the hypothesis that γ′ fibrinogen influences CVD events through its prothrombotic properties. Rather, γ′ fibrinogen concentrations seem to reflect general inflammation that accompanies and may contribute to atherosclerotic CVD, instead of γ′ fibrinogen being a causal risk factor. Abstract : Supplemental Digital Content is available in the text.